Children with Developmental Disabilities and their Motivation to Play - Lindsey Askins; Brittany Diasio; Dagmara Szewerniak; Susan M. Cahill Ph.D., OTR/L (Scholarworks @ WMU, 2013)
The purpose of this qualitative study was to examine how and when children with developmental disabilities aged nine to 12 years spontaneously demonstrated play behaviors indicative of intrinsic motivation. Data was collected from six child participants and four parent participants through the use of the Pediatric Volitional Questionnaire (PVQ) and semi-structured photo-elicitation interviews. Overall, the children who participated in this study sought out play experiences with which they were familiar in their natural environments. Specifically, they sought out experiences that afforded them the opportunity to exercise control over their environment and create a sense of predictability. Each of the children assumed the role of "orchestrator" and conducted his or her engagement in play occupations. The children demonstrated some spontaneous play within their social environment; however, many developmentally age-appropriate behaviors were not observed.